The role of principal’s manajerial mindset in shaping educational marketing strategies: A case study of a private junior high school in Indonesia - Fitria, Rezki Nurma; Trihantoyo, Syunu; Windasari, Windasari; Setiawan, Aditya Chandra; Putra, Febri Wandha; Supriyanto, Achmad (Edelweiss Applied Science and Technology, 2024)
This study examines the principals’ managerial mindset and its impact on school marketing decisions. This research aims to describe managerial practices from a mindset perspective in making marketing decisions in private sector schools in Indonesia. This research was included in qualitative research design adopting a case study. Data was collected through interview techniques and observation and then analyzed interactively and descriptively. The research respondents consisted of private junior high school residents in East Java. The research findings highlight the mindset aspects of managerial decisions that determine the major impact of goals and operations on marketing decisions. The results recommend that leadership organizations should be driven by a growth mindset in managerial practices to determine decision strategies particularly in marketing. Future research focuses on managerial mindset by considering external factors such as organizational policies and budgetary resources to provide a comprehensive understanding of the impact on strategic decision making.